ANALISIS KEBUTUHAN PENUNTUN PRAKTIKUM SEBAGAI BAHAN PENUNJANG PEMBELAJARAN KIMIA BERBASIS KETERAMPILAN PROSES SAINS - Maryam Jamilah; Nurfajriani Nurfajriani; Ramlan Silaban (PROSIDING SEMINAR KIMIA, 2022)
The education system is expected to be able to prepare a learning system that is in accordance with the development of students' career needs. The system can be developed based on skills and competencies that students will also need in the future, especially in science process skills. This study aims to analyze the need for a practicum guide as a support for science process skills-based learning. The type of research conducted is descriptive qualitative research with the Research and Development (R&D) method with the ADDIE development model. The research variables include an analysis of teaching needs and an analysis of the suitability of Core Competencies (KI) and Basic Competencies (KD) to determine competency indicators (GPA) which will be a reference in developing practical instructions based on science process skills. Research shows that the practicum guides currently used are limited to students' ability to follow procedures and do not provide opportunities for students to design predetermined experiments. Based on the results of these studies, it can be concluded that it is necessary to develop a practical guide based on science process skills as a support for the success of chemistry learning both in product, process, and performance skills. Keywords: Practical guidelines, Science Process Skills, R&D, ADDIE